The menu [videorecording (DVD)] - Reiss, Seth; Tracy, Will, 1983-; Fiennes, Ralph; Taylor-Joy, Anya, 1996-; Hoult, Nicholas, 1989-; Chau, Hong, 1979-; McTeer, Janet; Birney, Reed, 1954-; Light, Judith, 1949-; Leguizamo, John; Adelstein, Paul; Carrero, Aimee, 1988-; et al. (Searchlight Pictures, 2023)
A young couple travels to a secluded island to eat at an exclusive restaurant where the chef has prepared an extravagant menu. What they don't know is tonight's clientele have been selected for a specific reason, and they are all involved in the spectacle he intends to perform.